RANCANG BANGUN APLIKASI SELEKSI BAHAN PUSTAKA PADA BADAN PERPUSTAKAAN DAN KEARSIPAN PROVINSI JAWA TIMUR - Wahyu Dwi Putra; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2015)
The Library and Archives of East Java Province aims to provide the collections as a material to be read, heard and watched by library users who come to the library. The problem faced is in giving the collection to meet the needs of library users is very slow because the selection process is still done manually. To overcome these obstacles, the solution that is needed is the creation of applications the selection of library materials that can accelerate the selection process of library materials. Making these applications follow the stages of the SDLC (System Development Life Cycle) waterfall model. Based on trials that have been done, the application can generate procurement proposals as guidance in the purchase of library materials. This application can help agencies, especially the selection team to meet the needs of library users. Keywords : Selection Process, Library Users, Collection of Libraries